Differential regulation of MMP-13 expression in two models of experimentally induced periodontal disease in rats - de Aquino, Sabrina Garcia [UNESP]; Guimaraes, Morgana Rodrigues [UNESP]; Stach-Machado, Dagmar Ruth; Francisco da Silva, Juliete Aparecida; Spolidório, Luis Carlos [UNESP]; Rossa, Carlos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Objective: Evaluate expression of MMP-13 during the course of two models experimentally induced periodontal disease in rats.Design: Expression of MMP-13 at mRNA and protein levels was studied, respectively, by reverse transcription polymerase chain reaction (RT-PCR) and Western blotting. Two experimental models were used: LPS injections and ligature placement. 30 jig of LPS from Eschericia coli was injected twice a week into the palatal aspect of upper molars. Ligatures were placed at the gingival margin around lower first molars. Controls received injections of PBS vehicle and no ligatures on lower molars. Samples were collected 5,15 and 30 days after initiation of periodontal disease and processed for extraction of total RNA, total protein, and routinely processed for histology.Results: Both experimental models produced a significant increase on the inflammatory infiltrate that paralleled elevated levels of MMP-13 mRNA and protein at 5 and 15 days. The LPS model was associated with a sustained level of inflammation and increased MMP-13 mRNA throughout the 30 days, whereas the ligature model showed a decrease on the severity of inflammation and MMP-13 mRNA at the 30-day period. interestingly, MMP-13 protein levels were diametrically contrary to the mRNA levels.Conclusion: MMP-13 expression during LPS- and ligature-induced experimental periodontal disease follows the increase on severity of inflammation at the earliest periods. At 30 days, there is a decrease on the severity of inflammation on the ligature model associated with decreased MMP-13 mRNA. There is a lack of transcription-translation coupling of MMP-13 gene in both experimental models. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: MMP-13; Collagenase; Periodontal disease; Experimental models